The Effect of Turnover Intention, Locus of Control, Audit Fee, Work Motivation on the Performance Quality of Medan City Public Accountant Firm - Basa, Holy Maria; Yanti, Lidia Yuni; Br. Pinem, Delvi Meilani; Munthe, Dora Kristyna; Lilia, Wirda (SENTRALISASI, 2022)
The purpose of this study is to determine the effect of turnover intention, locus of control, audit fees, and work motivation on the quality of auditor performance at the Medan City Public Accounting Firm in 2021. The choice of the sector in this study is due to very tight competition conditions like now. In this case, the auditor must always maintain their performance so that audit quality is not compromised. Auditors must perform work by professional standards so that trust in the auditor can be maintained. The data used is sourced from quantitative data in the form of questionnaires. Using the Simple Random Sampling technique, a sample of 50 auditors was drawn from five Medan City KAPs.The results showed that locus of control, audit fees, and work motivation had a positive and significant effect on the quality of auditor performance at KAP Medan City. Meanwhile, the turnover intention has a negative effect and does not significantly affect the quality of auditor performance at KAP Medan City. But all variables are affected simultaneously.Â